KEPEMIMPINAN SEKOLAH DI ERA DIGITAL: STUDI KUALITATIF STRATEGI KEPALA SEKOLAH DALAM MENGELOLA PERUBAHAN - Anam, Syaiful; Habibi, Nur Syakherul; Firdaus, Sukma Umbara Tirta (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
ABSTRACT Digital transformation in education demands a fundamental shift in the way schools are managed, particularly at the leadership level. Principals, as learning leaders, are required not only to understand technology but also to strategically manage organizational culture change. This study aims to uncover principals' leadership strategies in managing digital-based change at the junior high school level. The approach used was a qualitative interpretive approach with a multiple case study design, involving principals from public and private junior high schools in Pakong District, Pamekasan Regency, who have experience in digital transformation. Data collection techniques included in-depth interviews, limited observation, and documentation studies. Data analysis was conducted using the Miles and Huberman model, while validity was maintained through triangulation of sources and methods. The study's findings are divided into three main themes. First, the meaning of digital leadership is reflectively interpreted by principals as the ability to integrate technological vision with participatory leadership values. Second, the managerial strategies employed include strengthening teacher capacity, digitizing standard operating procedures (SOPs) and quality control, and optimizing digital communication platforms. Third, the main challenges faced are teacher resistance, infrastructure inequality, and resource limitations, but these are offset by innovative solutions and local best practices. This study provides theoretical contributions to the development of a locally context-based digital leadership model, as well as practical implications for policymakers designing programs to improve the capacity of school principals to manage change in the digital era. ABSTRAK Transformasi digital dalam pendidikan menuntut pergeseran mendasar dalam cara sekolah dikelola, khususnya pada level kepemimpinan. Kepala sekolah sebagai pemimpin pembelajaran dituntut tidak hanya mampu memahami teknologi, tetapi juga mengelola perubahan budaya organisasi secara strategis. Penelitian ini bertujuan untuk mengungkap strategi kepemimpinan kepala sekolah dalam mengelola perubahan berbasis digital di tingkat sekolah menengah pertama. Pendekatan yang digunakan adalah kualitatif interpretatif dengan desain studi kasus multipel, melibatkan kepala sekolah dari SMP negeri dan swasta di Kecamatan Pakong, Kabupaten Pamekasan, yang telah memiliki pengalaman dalam transformasi digital. Teknik pengumpulan data mencakup wawancara mendalam, observasi terbatas, dan studi dokumentasi. Analisis data dilakukan dengan model Miles dan Huberman, sedangkan validitas dijaga melalui triangulasi sumber dan metode. Temuan studi ini terbagi dalam tiga tema utama. Pertama, makna kepemimpinan digital dimaknai secara reflektif oleh kepala sekolah sebagai kemampuan mengintegrasikan visi teknologi dengan nilai-nilai kepemimpinan partisipatif. Kedua, strategi manajerial yang digunakan meliputi penguatan kapasitas guru, digitalisasi SOP dan kontrol mutu, serta optimalisasi platform komunikasi digital. Ketiga, tantangan utama yang dihadapi adalah resistensi guru, ketimpangan infrastruktur, dan keterbatasan sumber daya, namun diimbangi oleh solusi inovatif dan praktik baik lokal. Studi ini memberikan kontribusi teoritis pada pengembangan model kepemimpinan digital berbasis konteks lokal, serta implikasi praktis bagi pengambil kebijakan untuk merancang program peningkatan kapasitas kepala sekolah dalam mengelola perubahan di era digital.